PERKEMBANGAN KEADAAN JALAN HUTAN MENURUT WAKTU DAN HUBUNGANNYA DENGAN POTENSI EROSI TANAH - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An investigation of the development of forest road condition in relation to soil erosion potential was carried out at four logging companies in South Kalimantan in 1989 to find the potential of forest roads in erosion processes after constructed and continually used, or abandoned for various years. The condition of road elements especially those related to factors stated in the Universal Soil Loss Equation were recorded and, based on this information, the category of specific roads in erosion potentials was decided subjectively to either one of very small, small, medium, rather large, and large. From the results, the following conclusions may be withdrawn:In general, erosion potentials of forest roads is decreased with time due to the growth of various vegetation and the process of natural soil stabilization.For continually used main roads, erosion potentials after about 2 years are still rather large to large; after 3-6 years are medium; and beyond 6 yers are very small to small. If main roads are totally abandoned, erosion potentials after left around one year are rather large; after 2-3 years are small to medium; and beyond 3 years are very small.For branch roads, erosion potentials for those abandoned up to one year are rather large to large; abandoned 2 - 3 years are medium to rather large; beyond 3 years are very small to small. For skidding roads that constructed by clearing vegetation only or vegetation, litter and top soils all together, when abandoned one year or more, they were densely couered by vegetation and for litter and, therefore, their erosion potentials are very small to small. Erosion potential tendency for skidding roads constructed by soil cutting and filling is almost the same as that in branch roads.Logging company practices outside Java showed that they are lacking in the knowledge of soil erosion, soil stability, drainage structures, and using vegetation for covering soil surfaces, all of which are important in minimizing environmental disturbances due to road construction activities.